(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
Albizia procera (Roxb.) Benth., a versatile and fast-growing tree species under the family Fabaceae, holds substantial potential for advancing sustainable development and climate resilience. This review highlights the taxonomy, ecological benefits, and diverse applications and ecological benefits of A. procera, emphasizing its role in reforestation, agroforestry, and sustainable forestry practices. A. procera is also valued for its high-quality timber, contributing to traditional woodworking and modern engineered products like Glulam beams, demonstrating its economic value. Additionally, A. procera contributes to its carbon sequestration, aligning with climate action goals due to its high biomass productivity. While acknowledging the need for careful management to mitigate risks such as invasiveness, this review underscores the significance of A. procera in fostering ecological restoration, sustainable livelihoods, and climate adaptation strategies. Its multifaceted benefits position A. procera as a critical asset in pursuing a sustainable and resilient future. Bangladesh J. Plant Taxon. 31(2): 329-347, 2024 (December)